Imaging Regional Lung Structure and Function in Small Animals Using Synchrotron Radiation Phase-Contrast and K-Edge Subtraction Computed Tomography - Bayat, Sam; Fardin, Luca; Cercos-Pita, José Luis; Perchiazzi, Gaetano; Bravin, Alberto (Frontiers in Physiology, 2022)
Synchrotron radiation offers unique properties of coherence, utilized in phase-contrast imaging, and high flux as well as a wide energy spectrum which allow the selection of very narrow energy bands of radiation, used in K-edge subtraction imaging (KES) imaging. These properties extend X-ray computed tomography (CT) capabilities to quantitatively assess lung morphology, and to map regional lung ventilation, perfusion, inflammation, aerosol particle distribution and biomechanical properties, with microscopic spatial resolution. Four-dimensional imaging, allows the investigation of the dynamics of regional lung functional parameters simultaneously with structural deformation of the lung as a function of time. These techniques have proven to be very useful for revealing the regional differences in both lung structure and function which is crucial for better understanding of disease mechanisms as well as for targeting treatment. Here, synchrotron radiation imaging methods are described and examples of their application to the study of disease mechanisms in preclinical animal models are presented.